2022
DOI: 10.1039/d2fo02300h
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effect of the polysaccharides from Astragalus membranaceus on type 2 diabetic mice based on the “gut microbiota–mucosal barrier”

Abstract: Astragalus membranaceus polysaccharide (APP), the main active constituent possesses numerous bioactivities. In this research, the T2DM model mice was combined with streptozotocin to study the hypoglycemic effect and mechanism of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Previous data have already described that an increase of Allobaculum was associated with the reduction of blood sugar in T2DM mice. 40 Moreover, several studies have shown that Allobaculum and Dubosiella are producers of SCFAs (such as propionic acid and butyric acid) and could alleviate inflammatory response. [41][42][43][44] In our research, the relative abundance of some of the genera, such as Blautia, Ruminococcus and Clostridium, was notably reduced in alcohol-fed mice, which was positively related to the integrity of the intestinal barrier.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Previous data have already described that an increase of Allobaculum was associated with the reduction of blood sugar in T2DM mice. 40 Moreover, several studies have shown that Allobaculum and Dubosiella are producers of SCFAs (such as propionic acid and butyric acid) and could alleviate inflammatory response. [41][42][43][44] In our research, the relative abundance of some of the genera, such as Blautia, Ruminococcus and Clostridium, was notably reduced in alcohol-fed mice, which was positively related to the integrity of the intestinal barrier.…”
Section: Food and Function Papermentioning
confidence: 99%
“…It has been reported that the relative abundance of Allobaculum was positively correlated with the concentration of anti-inflammatory mediator 3-hydroxyoctadecaenoic acid in the colon. 36 A selective increase in the Allobaculum level via the administration of Astragalus membranaceus polysaccharides 37 could suppress inflammatory infiltration as well as oxidative stress in the colon, ultimately protecting against intestinal barrier. Similarly, Romboutsia was reported to be decreased in HFD-fed mice, and intervention of yeast β-glucan 38 and Radix Puerariae thomsonii polysaccharide 39 could reverse this detrimental change and enhance TJ formation as well as mucus production in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previously published method, 16S rRNA high-throughput sequencing was performed on the high-variance region (V3–V4) in the stool samples. In brief, we utilize OMEGA Soil DNA kit (Norcross, GA, USA) to obtain DNA from stool samples.…”
Section: Methodsmentioning
confidence: 99%